ANALISIS PENGARUH KECERDASAN INTRAPERSONAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI BENTUK ALJABAR - Marfiah, Dewi Yuni; Pujiastuti, Heni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This study aims to describe students' mathematical communication skills in terms of their intrapersonal intelligence. This type of research used in this study is a descriptive study using a qualitative approach with as many as 5 people using purposive sampling techniques. In order to obtain the data needed in this study, data collection took the form of tests of mathematical communication skills with algebraic form material, and intrapersonal intelligence questionnaires. The data obtained in the form of data from test results and questionnaires, then the data are analyzed and concluded. Overall the results of tests that were followed by 5 students had mixed results. Furthermore, research subjects were taken to take a written test of mathematical communication skills. Each subject was taken 3 out of 5 students. Based on the results of the study it can be concluded that research subjects who have high intrapersonal intelligence will look superior in their mathematical communication skills. This is because they prefer to interpret understanding by managing and controlling themselves. As for students with abilities that are categorized as low and moderate they can also be intelligent in other types of intelligence and other factors that influence it. Therefore, teachers must pay more attention to each intelligence possessed by students and must apply appropriate learning methods.